1996
DOI: 10.1073/pnas.93.22.12559
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids modulate sodium and calcium currents in CA1 neurons.

Abstract: Recent evidence indicates that long-chain polyunsaturated fatty acids (PUFAs) can prevent cardiac arrhythmias by a reduction of cardiomyocyte excitability. This was shown to be due to a modulation of the voltage-dependent inactivation of both sodium (INa) and calcium (ICa) currents. To establish whether PUFAs also regulate neuronal excitability, the effects of PUFAs on INa and ICa were assessed in CAl neurons freshly isolated from the rat hippocampus. Extracellular application of PUFAs produced a concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
175
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(193 citation statements)
references
References 31 publications
15
175
1
2
Order By: Relevance
“…This fact is due to their favorable biophysical properties such as high motility and motional freedom (20)(21)(22)(23). DHAcontaining phospholipid molecular species might affect the blood-brain barrier (24), neurotransmission (4,22,25), or ionic channels (26,27). However, all of our knowledge on biophysical properties of membranes is based on results obtained on choline phosphoglycerides.…”
Section: Molecular Speciesmentioning
confidence: 96%
“…This fact is due to their favorable biophysical properties such as high motility and motional freedom (20)(21)(22)(23). DHAcontaining phospholipid molecular species might affect the blood-brain barrier (24), neurotransmission (4,22,25), or ionic channels (26,27). However, all of our knowledge on biophysical properties of membranes is based on results obtained on choline phosphoglycerides.…”
Section: Molecular Speciesmentioning
confidence: 96%
“…In young animals oxidative stress can raise the level of brain cholesterol to the level of aged rats [29]. One possible mechanism to the harmful effects of the oxidative stress is the finding that the stress induced an increase in lipid peroxidation by ATP via Ca 2+ [22,26,120]. Some successful efforts to correct the effects of the stress via special food supplements have been reported [11,12,[57][58][59][60]119], including PUFA supplements that can reverse the alcohol effects on the membrane [81], and increase the activity of certain membrane bound enzymes in different brain areas [110].…”
Section: Oxidative Stress-free Radicalsmentioning
confidence: 99%
“…Physiologic experiments, for example, have demonstrated that DHA or an anandamide analog of DHA has a potent effect on the K + channel (91)(92)(93). Leaf and co-workers showed that the nonesterified form of DHA has a potent effect on Na + (94)(95)(96) and Ca 2+ channels (96,97). Also, synaptic transmission (98) and long-term potentiation (99,100) in the hippocampus as well as N-methyl-D-aspartate responses in the cerebral cortex (101) are altered by DHA.…”
Section: Mechanisms Of Action Of Dhamentioning
confidence: 99%